2016
DOI: 10.1182/blood.v128.22.622.622
|View full text |Cite
|
Sign up to set email alerts
|

Polatuzumab Vedotin Combined with Obinutuzumab for Patients with Relapsed or Refractory Non-Hodgkin Lymphoma: Preliminary Safety and Clinical Activity of a Phase Ib/II Study

Abstract: Introduction: Previously reported results from this ongoing study showed clinical activity for polatuzumab vedotin (PoV), an antibody drug conjugate (ADC) containing the anti‐mitotic MMAE targeting CD79b, at a dose of 2.4 mg/kg, in combination with rituximab (R) in relapsed/refractory (r/r) diffuse large B‐cell lymphoma (DLBCL) and follicular lymphoma (FL) when patients (pts) were treated until progression (Morschhauser ASH 2014, Advani ASCO 2015). Obinutuzumab (G) is a next generation antiCD20 mAb with enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Patient demographics and baseline characteristics for each study are reported elsewhere [8,9,[19][20][21][22][23]; they were generally similar across treatment arms and ethnic subgroups. The numbers of Asian and non-Asian patients by race and region for the five studies are shown in Supplementary Table 1 (Online Resource 1).…”
Section: Demographicsmentioning
confidence: 99%
“…Patient demographics and baseline characteristics for each study are reported elsewhere [8,9,[19][20][21][22][23]; they were generally similar across treatment arms and ethnic subgroups. The numbers of Asian and non-Asian patients by race and region for the five studies are shown in Supplementary Table 1 (Online Resource 1).…”
Section: Demographicsmentioning
confidence: 99%
“…The potential for PK DDI between CHP and pola was evaluated using exposure comparisons between patients receiving pola + R/G-CHP and those with R/R DLBCL or FL receiving pola with R/G in a phase II study [17,35]. Exposure comparisons included cycle 1 C max and AUC of each pola analyte including acMMAE and unconjugated MMAE.…”
Section: Potential Pk Drug-drug Interaction Of Pola and R/g-chpmentioning
confidence: 99%
“…43 In the adult phase I trial of 25 patients with R/R DLBCL treated at the recommended phase II dosing, there were 4 CRs and 10 PRs. 56 Polatuzumab vedotin has subsequently been combined with rituximab, 56 obinutuzumab, 57 and bendamustine and rituximab or obinutuzumab 58 for patients with R/R DLBCL. In the latter study, 58 with a mean follow-up of 30 months, 9 of 19 responders remained event-free.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%